Impact of Good Governance on Social and Economic Development in Rwanda (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study was assessed the impact of good governance on social and economic development in Rwanda. The specific objectives: To determine the impact of good governance on social and economic development brought by Rwanda Governance Board; To analyze challenges facing good governance for social and economic development at Rwanda Governance Board and To establish relationship between good governance and social-economic development in Rwanda. This study was designed as a case study of Rwanda Governance Board using the survey method; a case study was described as analysis of the impact of good governance on social and economic development in Rwanda, assuming that the researcher acquired knowledge regarding the subject under review from in-depth exploration of a single case. It was qualitative analysis that involves careful observation of a situation. All the respondents from the population of different sectors to respond to research questionnaires. The researcher used questionnaires to collect data, As far as this study was concerned, the population was comprised by 145 employees, administrators and policy makers from Rwanda Governance Board. To describe target population of a study as the point of focus from which a generalization was made regarding the research findings. Thus, a sample size of 60 respondents as citizens and staffs from three sectors were considered representative of the total population. I used primary and secondary data to get all information needed in this study, the quantitative data was analyzed using descriptive and inferential statistics after running the data collected through the Statistical Package for Social Sciences (SPSS). The first research objective or research question was to determine the impact of good governance on social and economic development brought by Rwanda Governance Board, the findings of the study discovered that good governance has major contributed to the development of the rest of socio-economic sectors in the country. However, the results of the study shows that the whole civil servants’ been taking part the bad governance which led in destruction of social development, but the responsibility of that bad things have taking the government workers. The second research objective or research question where was to analyze challenges facing good governance for social and economic development at Rwanda Governance Board, therefore the findings of the study exposed that there were a lot of consequence of lack or bad governance which caused corruption fraud and embezzlement, on the other hand public lost their confidence of government institutions. Finally the research objective or research question were understand the significance relationship between good governance and social-economic development in Rwanda, the nature an administrative requirement of good governance may be poorly understood both by the top government organizations and the civil servants besides that the general weakness of accountability and luck of transparency are the challenges of good governance in RGB, besides that most of politicians and civil servant and community members admitted the importance of applying the principal of good governance to enhance economic and social development. Firstly, by in a straight line forthcoming legislative body of the influential as well as civil society, should maintain and implement the principles of good governance to eliminate to rebuild and develop for the country and its people. Secondly, civil servants and politicians should change their attitude through driving fuel for bad governance in the country to eradicate to poverty, in order to create employment opportunities. Thirdly, since there is lack of the principles of good governance, government should establish and implement in a quality control systems be done which will assure transparency and efficiency, also to increase economic development must improve the economic mechanism whose focus is to renew mechanisms and policies so as to release radically productive forces, expand domestic and foreign markets in order to get well infrastructures.